1991
DOI: 10.1007/bf00360529
|View full text |Cite
|
Sign up to set email alerts
|

Differential mechanisms governing segregation of a univalent in oocytes and spermatocytes of Drosophila melanogaster

Abstract: In tricomplex heterozygotes in Drosophila melanogaster three metacentric autosomes (the TRI chromosomes) appear as a trivalent in meiosis while one autosome consisting of two homologous arms attached to the same centromere (a compound) behaves as an obligatory univalent. Cytological analysis of meiosis of tri-complex heterozygotes indicates that in oocytes the univalent compound behaves non-independently in relation to segregation of the trivalent. The compound is distributed preferentially to the same pole as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
2

Year Published

1992
1992
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
4
13
2
Order By: Relevance
“…A previous genetic model (Grell, 1976) postulated that distributive segregation involved a second round of pairing and segregation which followed the segregation of exchange chromosomes. Our data and previous cytological studies (Puro and Nokkala, 1977;Kimble and Church, 1983 ;Puro, 1991) are not consistent with a second round of pairing, as nonexchange chromosomes are positioned toward opposite poles before the spindle has fully formed . More recently, Carpenter (1991) has proposed that nonexchange homologs are linked by a microtubule bridge which substitutes for chiasma .…”
Section: The Cellular Basis Of Distributive Segregationcontrasting
confidence: 99%
See 1 more Smart Citation
“…A previous genetic model (Grell, 1976) postulated that distributive segregation involved a second round of pairing and segregation which followed the segregation of exchange chromosomes. Our data and previous cytological studies (Puro and Nokkala, 1977;Kimble and Church, 1983 ;Puro, 1991) are not consistent with a second round of pairing, as nonexchange chromosomes are positioned toward opposite poles before the spindle has fully formed . More recently, Carpenter (1991) has proposed that nonexchange homologs are linked by a microtubule bridge which substitutes for chiasma .…”
Section: The Cellular Basis Of Distributive Segregationcontrasting
confidence: 99%
“…We have found that nonexchange chromosomes are positioned between the metaphase plate and the spindle pole in a bilaterally symmetric manner (Fig . 3), confirming the conclusion that these chromosomes are prepositioned toward the spindle poles (Puro and Nokkala, 1977 ;Puro, 1991 ;Kimble and Church, 1983) . The two fourth chromosomes, identifiable by their small size, are positioned between the metaphase plate and the poles, while the remaining chromosomes are tightly massed at the metaphase plate ( Fig .…”
Section: Chromosome Organization In Mature Oocytessupporting
confidence: 70%
“…The centrosomal protein, DMAP190 (CP190), was not found at the poles of the meiosis I spindle ( Theurkauf and Hawley 1992 ), but it has recently been reported to localize to a ring- or disk-shaped structure between the two tandem meiosis II spindles of Drosophila oocytes ( Riparbelli and Callaini, 1996 ). The ring-shaped structure in the central pole region of the Drosophila meiosis II spindles was observed previously ( Puro, 1991 ) and was suggested to function in pole organization for the second meiotic division. Nucleation and organization of microtubules for assembly of the Drosophila meiosis I and II spindles could therefore differ from one another and from anastral spindles of other organisms.…”
supporting
confidence: 69%
“…Most recently Puro (1991) has shown by means of cytological observations that in female meiosis of Drosophila melanogaster disjunction of both chiasmate and achiasmate chromosomes is predetermined by nonrandom arrangement of the centromeric regions of chromosomes in the chromocenter. Further, he suggests that this kind of system may be sensitive to disturbing factors affecting the internal organization of the chromocenter.…”
Section: Discussionmentioning
confidence: 99%
“…Such disturbing factors might be the presence of extrachromosomal elements, and the structural heterozygosity dealt with in the present study. According to Puro (1991), non-homologous pairing may be viewed as a kind of spatial arrangement of centromeric regions within the framework of the suprachromosomal organization, the chromocenter, characteristic of meiosis in oocytes in D. melanogaster.…”
Section: Discussionmentioning
confidence: 99%